HUBUNGAN SIKAP DAN MOTIVASI WANITA USIA SUBUR PADA PEMERIKSAAN IVA TEST DI WILAYAH KERJA PUSKESMAS NAGRAK - Patimah, Papat; Pratiwi, Julia; Fauziah, Sifa; Andira, Dilla Aprilia; Widiyasari, Siska (STIKES Permata Nusantara Cianjur, 2024)
Introduction: The Indonesian cancer organization states that cancer is one of the main causes of death throughout the world. In 2018, based on WHO data, cancer was the cause of death for around 207,210 people in Indonesia. Lung, liver, stomach, colorectal cancer, cervical cancer and breast cancer are the biggest causes of cancer deaths every year (Nawangwulan, 2021). Decree of the Minister of Health of the Republic of Indonesia number 796/MNEKES/SK/VII/2010 concerning national technical guidelines and adequate interventions through primary, secondary and tertiary prevention. This decision is related to the government's role in preventing cervical cancer, which is a deadly disease for sufferers (Nawangwulan, 2021). Various efforts that can be made to prevent cervical cancer include identifying and preventing risk factors, early detection of pre-cancer, and including new findings in the form of HPV vaccination. There are several examination methods that can be used to find pre-cancerous lesions, namely the IVA test, visual inspection with acetic acid (IVA), and so on. The most popular method is the pap smear. The IVA test is a cytological examination of cervical cancer and a portion of the test is recommended by experts because it is quite effective in identifying the presence of cancer cells (Bemj et al., 2020).Method: This type of research is quantitative research with a cross sectional design. The sampling technique used by this researcher was random sampling, with a sample size of 165 respondents, sampling based on clusters. Results: Statistical test resultsrank spearman The significant number or probability value obtained (0.000) is much lower than the significant standard of 0.05 or (p value<), because pvalue<, which means there is a relationship between the attitude and motivation of women of childbearing age couples and the IVA test.t Conclusion: Of the 165 respondents, almost all of them had a negative attitude but 64 respondents (86.5%) had moderate motivation. According to the researchers, the negative attitude of women of childbearing age regarding the IVA Test had an impact on the desire/desire or motivation of women of childbearing age to have the IVA Test. When respondents consider that the IVA Test examination is not important and do not think it is useful, they are reluctant to carry out the examination.